The Franco-German Parliamentary Assembly: a transnational accountability forum in a time of crisis?. Issue 3 (3rd July 2022) - Borońska-Hryniewiecka, Karolina; Kinski, Lucy
ABSTRACT: The Franco-German Parliamentary Assembly (FGPA) set up in March 2019 is the result of an unprecedented collaboration between the parliaments of the two most powerful member states of the European Union (EU). While this bi-parliamentary assembly has received some attention by political think tanks, we know very little about its potential transformative effect on bilateral executive accountability as well as on the accountability and the salience of EU economic governance in the context of the COVID-19 pandemic. Based on an extensive document analysis and on semi-structured interviews with FGPA members and staff, we show that to a large extent the FGPA has become a forum of transnational accountability that cuts across the traditional domestic and EU channels of executive oversight. Our findings also reveal that the pandemic has increased the FGPA's oversight activity and allowed for the (re-)emergence of EMU matters on the shared parliamentary and executive agenda.